2020
DOI: 10.1002/jmri.27455
|View full text |Cite
|
Sign up to set email alerts
|

Hyperperfusion on Arterial Spin Labeling MRI Predicts the 90‐Day Functional Outcome After Mechanical Thrombectomy in Ischemic Stroke

Abstract: Background The prognostic significance of hyperperfusion after reperfusion therapy in patients with acute ischemic stroke (AIS) remains controversial. Purpose To investigate the clinical factors associated with hyperperfusion, and the 90‐day prognostic value of hyperperfusion after mechanical thrombectomy in AIS patients. Study Type Retrospective. Population/Subjects Fifty‐four AIS patients who underwent mechanical thrombectomy. Field Strength/Sequence Time‐of‐flight MR angiography, pulsed arterial spin labeli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 33 publications
2
28
0
Order By: Relevance
“…Several studies have investigated the use of 3D-ASL to detect perfusion abnormalities in the context of infarction (Chen et al, 2016;Noguchi et al, 2016). Lu et al (2021) suggested that hyperperfusion on 3D-ASL correlated with successful recanalization and might be an independent prognostic marker for good neurological outcomes in patients with AIS. 3D-ASL can objectively show the development of collateral circulation around the infarcted area and provide an informed assessment of the disease and prognosis (Yuan et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have investigated the use of 3D-ASL to detect perfusion abnormalities in the context of infarction (Chen et al, 2016;Noguchi et al, 2016). Lu et al (2021) suggested that hyperperfusion on 3D-ASL correlated with successful recanalization and might be an independent prognostic marker for good neurological outcomes in patients with AIS. 3D-ASL can objectively show the development of collateral circulation around the infarcted area and provide an informed assessment of the disease and prognosis (Yuan et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…In a retrospective study of 54 EVT-treated patients, 36 patients showed hyperperfusion in the infarcted area on ASL-based scans at 4 days (median) after stroke onset, which was related to successful recanalization and associated with an improvement in NIHSS at 24 h. Hyperperfusion was, independently from successful recanalization, also associated with good functional outcome at 90 days post-stroke [40]. Potreck et al [41] visually graded hyperperfusion using DSC-MRI at 24 h after successful EVT in a prospective study of 38 patients who achieved complete recanalization (mTICI ≥ 2b).…”
Section: Hyperperfusion and Favorable Outcomementioning
confidence: 99%
“…Definition Hyperperfusion, which can be described by an increase of CBF of > 100% of baseline [38], sits at the other end of the reperfusion abnormality spectrum. Although formal definitions are lacking, some studies have applied CBF ≥ 130% of control (contralateral) values as hyperperfusion threshold [39,40], whereas other studies relied on qualitative assessment [41,42]. Tmax maps may theoretically be used to delineate areas of hyperperfusion, but threshold values have not been published.…”
Section: Post-recanalization Hyperperfusionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increased ASL signal post thrombectomy correlates with improved tissue and clinical outcomes. 45,46 ASL can also be helpful in EVT cases in assessing reperfused tissue as characterized by increased ASL signal in the previously hypoperfused tissue (Figure 7). Figure 7 demonstrates acute infarction in right frontal operculum.…”
Section: Asl Versus Dsc Perfusion Imagingmentioning
confidence: 99%